2020
DOI: 10.1021/acs.est.9b06984
|View full text |Cite
|
Sign up to set email alerts
|

Occupational Inhalation Exposures to Nanoparticles at Six Singapore Printing Centers

Abstract: Laser printers emit high levels of nanoparticles (PM0.1) during operation. Although it is well established that toners contain multiple engineered nanomaterials (ENMs), little is known about inhalation exposures to these nanoparticles and work practices in printing centers. In this report we present a comprehensive inhalation exposure assessment of indoor microenvironments at six commercial printing centers in Singapore, the first such assessment outside of the United States, using real-time personal and stati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
18
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 44 publications
(20 citation statements)
references
References 48 publications
2
18
0
Order By: Relevance
“…The daily geometric mean NP concentrations in copy centers in the Northeast USA ranged from 3700 to 34,000 particles/cm 3 , with emission peaks reaching up to 1.4 million particles/cm 3 and a count median diameter centered around 30 nm [10,11]. Similar findings were reported recently in Singaporean photocopy centers [12] and in chamber studies [3]. The composition of the nanoscale fraction (PM 0.1 or particulate matter less than 0.1 µm aerodynamic diameter) generated from the photocopiers has also been documented in three comprehensive studies [4,11,12] to include approximately 6-63% organic compounds (as organic carbon), <1% elemental carbon, and 2-8% metals.…”
Section: Introductionsupporting
confidence: 86%
See 2 more Smart Citations
“…The daily geometric mean NP concentrations in copy centers in the Northeast USA ranged from 3700 to 34,000 particles/cm 3 , with emission peaks reaching up to 1.4 million particles/cm 3 and a count median diameter centered around 30 nm [10,11]. Similar findings were reported recently in Singaporean photocopy centers [12] and in chamber studies [3]. The composition of the nanoscale fraction (PM 0.1 or particulate matter less than 0.1 µm aerodynamic diameter) generated from the photocopiers has also been documented in three comprehensive studies [4,11,12] to include approximately 6-63% organic compounds (as organic carbon), <1% elemental carbon, and 2-8% metals.…”
Section: Introductionsupporting
confidence: 86%
“…Similar findings were reported recently in Singaporean photocopy centers [12] and in chamber studies [3]. The composition of the nanoscale fraction (PM 0.1 or particulate matter less than 0.1 µm aerodynamic diameter) generated from the photocopiers has also been documented in three comprehensive studies [4,11,12] to include approximately 6-63% organic compounds (as organic carbon), <1% elemental carbon, and 2-8% metals. Polycyclic aromatic hydrocarbons (PAHs) species, including phenanthrene, fluoranthene, pyrene, chrysene, and benzo(b)fluoranthene at concentrations from 2-10 ng/m 3 have been quantified in printer-and copier-emitted NPs [4,12,13].…”
Section: Introductionsupporting
confidence: 82%
See 1 more Smart Citation
“…Although the concentrations are high in comparison to ambient levels, they are comparable to several other working environments. For instance, personal exposure measurements by Setyawati et al at a printing center revealed a maximum exposure of 220 µm 2 cm -3 (Setyawati et al, 2020). The worker with highest exposure levels had an overall mean exposure of 106 µm 2 cm -3 .…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…Studies conducted in working environments and indoor conditions have measured LDSA e.g. to characterize LDSA exposure in printing centers (Setyawati et al, 2020) or to study influence of air cleaner devices to LDSA in offices (Küpper et al, 2019). In ambient air the LDSA concentrations typically vary from ~10-50 µm 2 cm -3 measured at clean background areas (Kuula et al, 2020), to values up to ~100-150 µm 2 cm -3 typically observed near PM sources such as roads (Cheristanidis et al, 2020;Leavey et al, 2017).…”
Section: Accepted Manuscriptmentioning
confidence: 99%